Development of Simulated Educational Joint Mobilization Module Using Leap Motion Controller (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Joint mobilization is a complicated task in terms of learning as well as teaching and ischaracterized by great inter subject variability. With reference to the acquisition of skills such as jointmobilisation, only a few studies have investigated the effectiveness of the provision of real-time visualfeedback on a computer screen in terms of students’ ability to establish optimal force and demonstrateadequate performance. There is lack of training in theory and practical skills in mobilization given to thePhysiotherapy students. Thus, an effort has been made in to practice it virtually using Leap Motion Controller.Method: Total 138 participants will be recruited as per the inclusion and exclusion criteria. A briefexplanation about the study will be given. Participants will be given exposure to the software and modalitybeing used along with demonstration. Followed by, a questionnaire to evaluate the effective learning usingthe System Usability Scale.Conclusion: The results from the study will significantly provide efficacy of the simulative device andevidence on the use of LMC for learning joint mobilization using the System Usability Scale.
Keywords: Biomechanics, Glenohumeral Joint, Mobilization, Shoulder Joint, Simulation